Dimensions of Cooperative Learning: Practical Experiences - Fuentesal García, Julio; López-Beltrán, Daniel Pastor (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2019)
This paper presents a methodological proposal to promote educational innovation through eight activities carried out at Don Bosco Vocational School with the students from both the Higher Level Education Cycle in Teaching and Socio-physical Animation and the Higher Level Education Cycle in Early Childhood Education. Firstly, cooperative work and its dimensions are described, with a special focus on the game as a means to carry out cooperative activities during the teaching-learning process and as a tool to promote coexistence. Secondly, in order to motivate the students from the beginning of the session until its completion, it is proposed a different use of the resources inside the classroom. Thirdly, different activities that have been carried out in this practical experience are displayed, since they can be adapted to the needs of the different educational stages from primary education to university levels.
Keywords: cooperative learning; games; coexistence